The Internal Pressure Test in Experiment and Simulation—Influence of the Wall Thickness Variation and the Change of the Packaging Behavior after the Impact of Standard Liquids. (6th July 2012) - Menrad, Andreas; Goedecke, Thomas; Gruender, Klaus‐Peter; Wagner, Manfred H.
<x xml:space="preserve">Abstract</x> The effect of the wall thickness variation of blow‐moulded bodies made of high‐density polyethylene on an internal pressure test after prestoring the packaging with standard liquids was evaluated in experiments and simulations. The objects of the investigation were jerrycans used for the transportation and storage of dangerous goods. The wall thickness was determined using two alternative methods to the magnetostatic measurement. These alternative methods are used for research purpose to get a volumetric model of the jerrycan wall as a geometric model for the simulation. The comparison of the experiments and the simulations of the internal pressure test were performed using the digital image correlation method. The integral strain and deformation of the whole jerrycan was detected by measuring the total mass of the jerrycan being filled with water during the internal pressure test. This is a suitable alternative to the optical measurements of local deformation by the digital image correlation method. Prestorage at 40 °C without the influence of chemicals strengthens the jerrycan, whereas the swelling effect of butyl acetate and hydrocarbon mixture softens the jerrycan. The comparison with the experiment is necessary to verify the accuracy of the simulation. It shows that the deformation can be simulated more precisely by using the actual measured geometry. The weakening of the high‐density polyethylene caused by a hydrocarbon mixture can be simulated using the Arrhenius equation. The aim of the simulation was to discover whether it is possible to use specimens to predict the behaviour of a packaging both after the influence of standard liquids. Copyright © 2012 John Wiley & Sons, Ltd.